IMPLEMENTASI KONSEP TA’DĪB DALAM PENDIDIKAN ISLAM UNTUK MEWUJUDKAN SISWA YANG BERKARAKTER - Maria Ulfah (Universitas Islam Negeri Ar-Raniry, 2011)
The concept of education according to Islamic perspective, whether formal, informal, or non formal education, basically not only intended to give students knowledge or skills, but also to make them having social and spiritual quotients. It is that will make them to be excellent persons (insÄn kÄmil). According to the philosophy of islamic education there are three terms denote the meaning of education i.e tarbiyah, taâ€™lÄ«m and taâ€™dÄ«b. The last term is more appropriate to use, since covers knowledge and values to be transfered to students.